Design science and neuroscience: A systematic review of the emergent field of Design Neurocognition. (January 2023) - Balters, Stephanie; Weinstein, Theresa; Mayseless, Naama; Auernhammer, Jan; Hawthorne, Grace; Steinert, Martin; Meinel, Christoph; Leifer, Larry J.; Reiss, Allan L.
Abstract : Design Neurocognition is an emerging research field that aims to elucidate the "black-box" of a designer's mind through the use of brain imaging tools such as electroencephalography (EEG), functional near-infrared spectroscopy (fNIRS) and magnetic resonance imaging (MRI). More than a decade worth of study has led to many interesting research findings. Here, we systematically review the existing literature in the field. We identify 82 publications and provide an overview of nine main research topics that have been studied. We uncover a large variety of methodological approaches that currently hamper the evaluation of research findings through meta-analysis. Finally, we provide recommendations to advance the field and collaboratively generate a more complete understanding of human behavior during design activities. Highlights: Design Neurocognition aims to elucidate the "black-box" of a designer's mind through the use of brain imaging tools. In our systematically review, we identify 82 publications and provide an overview of nine main research topics that have been studied. We uncover a large variety of methodological approaches that currently hamper the evaluation of research findings through meta-analysis. Finally, we provide recommendations to advance the field of Design Neurocognition.